Mapping media accountability in stateless nations: The case of Catalonia. Issue 2 (1st October 2016) - Almiron, Núria; Narberhaus, Marta; Mauri, Marcel
This article draws on the results of a research project on media accountability instruments in Catalonia. We map out media accountability in Catalonia focusing on institutional self-regulation instruments and outline their history compared to that of equivalent instruments in the rest of Spain and Europe. We discuss how the situation in Catalonia differs significantly from that of Spain in the context of Hallin and Mancini's media systems models. We argue that including the cultural domain in an analysis of media accountability provides a more accurate understanding of the media system in stateless nations. We conclude that the culture of journalistic accountability in Catalonia is more closely aligned with the Corporatist or Liberal model than with the Mediterranean one and thus that the economic and political spheres alone do not provide a true picture of national realities when assessing media accountability.